Z(gamma) production and limits on anomalous ZZ(gamma) and Z(gamma gamma) couplings in p(p)over-bar collisions at root s 1.96 TeV - Abazov, V. M.; Abbott, B.; Acharya, B. S.; Adams, M.; Adams, T.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; Alves, G. A.; Aoki, M.; Watts, G.; et al. (Amer Physical Soc, 2012)
We present a measurement of p (p) over bar -> Z gamma -> l(+)l(-)gamma (l = e, mu) production with a data sample corresponding to an integrated luminosity of 6.2 fb(-1) collected by the D0 detector at the Fermilab Tevatron p (p) over bar Collider. The results of the electron and muon channels are combined, and we measure the total production cross section and the differential cross section d(sigma)/dp(T)(gamma), where p(T)(gamma) is the momentum of the photon in the plane transverse to the beam line. The results obtained are consistent with the standard model predictions from next-to-leading order calculations. We use the transverse momentum spectrum of the photon to place limits on anomalous ZZ gamma and Z gamma gamma couplings.